2022
DOI: 10.3389/fmolb.2022.863099
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating GPCR Drug Discovery With Conformation-Stabilizing VHHs

Abstract: The human genome encodes 850 G protein-coupled receptors (GPCRs), half of which are considered potential drug targets. GPCRs transduce extracellular stimuli into a plethora of vital physiological processes. Consequently, GPCRs are an attractive drug target class. This is underlined by the fact that approximately 40% of marketed drugs modulate GPCRs. Intriguingly 60% of non-olfactory GPCRs have no drugs or candidates in clinical development, highlighting the continued potential of GPCRs as drug targets. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 110 publications
0
19
0
Order By: Relevance
“…The expanding collection of Nbs that target GPCRs bodes favorably for these efforts. 37 ■ METHODS Synthesis. Peptides were synthesized using solid-phase synthesis with Fmoc protection of backbone amines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expanding collection of Nbs that target GPCRs bodes favorably for these efforts. 37 ■ METHODS Synthesis. Peptides were synthesized using solid-phase synthesis with Fmoc protection of backbone amines.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our success in leveraging Nb–epitope interaction for improving the potency of an already high affinity ligand suggests that this approach should be widely useful for basic biomedical research. The expanding collection of Nbs that target GPCRs bodes favorably for these efforts …”
Section: Resultsmentioning
confidence: 99%
“…This raises the question of the biological significance of such constraints for PK111195 binding site: does the apo form of the mTSPO need a large flexibility to bind so different ligands, such as isoquinoline and porphyrin? Among the biomolecules of medical interest, membrane proteins such as GPCR suffer from spectral crowding induced by conformational plasticity [70] that, for most of them, limits their access for NMR investigation. High-magnetic field and MAS spinning above 60 kHz rotation frequency demonstrated that sensitivity and 1 H resolution can be significantly improved, notably for microcrystalline proteins available in small amounts [71] but also for membrane proteins [41].…”
Section: Discussionmentioning
confidence: 99%
“…Methodological hurdles that linger the development of VHHs against GPCR, such as the selection of the antigen ( 90 ), the advantages of synthetic libraries versus libraries from immunized animal ( 40 , 91 , 92 ), the comparison of display methods ( 5 , 38 , 40 ) have been previously reported. Here, we focus on the specificities that make anti-GPCR intra-VHH expression inside the cell and characterization particularly challenging ( Figure 5 ).…”
Section: Methodological Limitations and Opportunitiesmentioning
confidence: 99%
“…Since anti-GPCR intra-VHHs stabilize selective conformations of the receptor, they have been named “confobodies”, a registered trademark of Confo Therapeutics ( 38 ). They can recognize intracellular regions of the receptor devoted to signal transduction ( Figure 1 ).…”
Section: Expected Insights Onto Gpcr Activity and Regulationmentioning
confidence: 99%